The Role of Education in the Formation of Character and Noble Morals from the Perspective of the Qur’an - Abdul Muid; Nasrulloh Nasrulloh (PT. Banjarese Pacific Indonesia, 2024)
This research aims to describe the role of education in the formation of noble character and morals based on the perspective of the Qur'an. The Qur'an as the main source of Islamic teachings emphasizes the importance of holistic education, which not only focuses on the intellectual aspect but also includes moral and spiritual development. The method used in this study is a literature study, by analyzing interpretations and related literature that discusses the relationship between education, morality, and character. The results of the study show that there are several implications in the formation of character and noble morals from the perspective of the Qur'an, such as: 1) Education as a process of self-purification (Tazkiyah), 2) Character formation through parental advice to children. 3) Building character with positive traits and attitudes. 4) Education as a process of noble moral development. This research concludes that education based on the principles of the Qur'an has a crucial role in creating individuals who are not only intellectually intelligent, but also have noble ethics, which ultimately contributes to the creation of a harmonious and civilized society.